2018
DOI: 10.3201/eid2407.180162
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Respiratory Viruses in Deceased Persons, Spain, 2017

Abstract: During the 2016–17 influenza season in Spain, we tested specimens from 57 elderly deceased persons for respiratory viruses. Influenza viruses were detected in 18% of the specimens and any respiratory virus in 47%. Only 7% of participants had received a diagnosis of infection with the detected virus before death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…However, our results showed that several respiratory viruses other than SARS-CoV-2 were also commonly found. These other viruses may be more frequently found in other seasons without dominance of SARS-CoV-2 [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, our results showed that several respiratory viruses other than SARS-CoV-2 were also commonly found. These other viruses may be more frequently found in other seasons without dominance of SARS-CoV-2 [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since only a small percentage of deceased people were usually tested for respiratory viruses before they died, the impact of respiratory viruses on mortality is not well known [ 1 , 18 ]. Furthermore, mortality statistics by cause of death largely underestimate the role of respiratory viruses in mortality [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Feasibility of post-mortem testing for detecting the presence of seasonal respiratory viruses in the community is demonstrated by Navascués et al (4). They identified respiratory viruses (including influenza virus A(H3N2), RSV (subgroups A and B), coronavirus (types 229E and OC43), and rhinovirus) in 47% of 57 deceased individuals in Navarre, Spain, despite only 7% being diagnosed prior to death (4).…”
Section: Introductionmentioning
confidence: 99%
“…Feasibility of post-mortem testing for detecting the presence of seasonal respiratory viruses in the community is demonstrated by Navascués et al (4). They identified respiratory viruses (including influenza virus A(H3N2), RSV (subgroups A and B), coronavirus (types 229E and OC43), and rhinovirus) in 47% of 57 deceased individuals in Navarre, Spain, despite only 7% being diagnosed prior to death (4). They conclude that reverse transcription PCR (RT-PCR) from nasopharyngeal swabs taken post-mortem provided a sufficiently sensitive method for detecting respiratory viruses in deceased individuals.…”
Section: Introductionmentioning
confidence: 99%